Synthesis, Photophysics, Computational Approaches, and Biomolecule Interactive Studies of Metalloporphyrins Containing Pyrenyl Units: Influence of the Metal Center. Issue 12 (23rd March 2022) - Hahn da Silveira, Carolina; Chaves, Otávio A.; Marques, Amanda C.; Rosa, Nathália M. P.; Costa, Luiz Antônio S.; Almeida Iglesias, Bernardo
Abstract: A classical methodology to design free‐base meso ‐tetra‐(1‐pyrenyl)porphyrin (H2 TPyrP ) and their corresponding metalloporphyrins containing Zn(II), Cu(II), Ni(II), Co(III), and Mn(III) was described. These porphyrins were characterized in terms of structure, photophysical, and interactions profile with calf‐thymus deoxyribonucleic acid (CT‐DNA) and bovine serum albumin (BSA). H2 TPyrP exhibited five characteristic bands in the visible wavelength: Soret (432 nm) and Q‐bands (520–650 nm range), while the metalloporphyrins showed some spectrum shifts according to the nature of the ion, which were also explored by time‐dependent density functional theory (TD‐DFT) calculations. The fluorescence and singlet oxygen quantum yield (Φfl, ΦΔ, respectively) decreased with the presence of metal species in the porphyrin core. The porphyrins interact spontaneously via a ground‐state association in the minor groove of CT‐DNA following the increasing order of binding: CuTPyrP <H2 TPyrP <CoTPyrP <MnTPyrP <NiTPyrP <ZnTPyrP, while for BSA the suitable complex geometry for Co(III) and Mn(III) complexes increased the binding capacity. Abstract : Meso ‐tetra‐(1‐pyrenyl)porphyrin containing Zn(II), Cu(II), Ni(II), Co(III), and Mn(III) were synthesized in good yield (45–90 %). The effects of ion nature on the photophysics and interaction with biomacromolecules were evaluated by the combination of experimental assays and theoretical calculations. The fluorescence and singlet oxygen quantum yield decreased as the biomacromolecule interactions increased with the presence of metal species in the porphyrin core.